Hypomethylation of human-specific family of LINE-1 retrotransposons in circulating DNA of lung cancer patients. (September 2016) - Gainetdinov, Ildar V.; Kapitskaya, Kristina Yu.; Rykova, Elena Yu.; Ponomaryova, Anastasia A.; Cherdyntseva, Nadezda V.; Vlassov, Valentin V.; Laktionov, Pavel P.; Azhikina, Tatyana L.
Highlights: MIRA detects hypomethylation of LINE-1 promoters in csbDNA of lung cancer patients. Level of hypomethylation is more pronounced for human-specific L1Hs family. ROC-curve analysis supports MIRA assay as a promising diagnostic tool. Abstract: Circulating DNA has recently gained attention as a fast and non-invasive way to assess tumor biomarkers. Since hypomethylation of LINE-1 repetitive elements was described as one of the key hallmarks of tumorigenesis, we aimed to establish whether the methylation level of LINE-1 retrotransposons changes in cell-surface-bound fraction of circulating DNA (csbDNA) of lung cancer patients. Methylated CpG Island Recovery Assay (MIRA) coupled to qPCR-based quantitation was performed to assess integral methylation level of LINE-1 promoters in csbDNA of non-small cell lung cancer patients (n = 56) and healthy controls (n = 44). Deep sequencing of amplicons revealed that hypomethylation of LINE-1 promoters in csbDNA of lung cancer patients is more pronounced for the human-specific L1Hs family. Statistical analysis demonstrates significant difference in LINE-1 promoter methylation index between cancer patients and healthy individuals (ROC-curve analysis: n = 100, AUC = 0.69, p = 0.0012) and supports the feasibility of MIRA as a promising non-invasive approach.